Role of MMP-2 (-1306 C/T) Polymorphism in Pituitary Adenoma - Brigita Glebauskiene; Rasa Liutkeviciene; Alvita Vilkeviciute; Loresa Kriauciuniene; Giedrimantas Bernotas; Arimantas Tamasauskas; Dalia Zaliuniene (Scientifica)
Purpose. To determine if the frequency of the genotype of MMP-2 (-1306 C/T) Rs243865 has an influence on the development of pituitary adenoma (PA). Methods. The study enrolled n=84 patients with PA and a random sample of the population n=318 (reference group). The genotyping test of MMP-2 (-1306 C/T) was carried out using the real-time polymerase chain reaction method. Results. Analysis of MMP-2 (-1306 C/T) gene polymorphism has not revealed any differences in the genotype (C/C, C/T, and T/T) distribution between the PA patients and the reference group (as follows: 50%, 44%, and 6% versus 59.75%, 33.96%, and 6.29%). MMP-2 (-1306) C/C genotype was rarely observed in noninvasive PA compared to healthy controls: 35.1% versus 59.75%; p=0.0049, as well C/C genotype being more frequently detected in nonrecurrence PA compared to healthy controls: 46.5% versus 59.75%; p=0.0468. MMP-2 (-1306) C/T genotype was more frequently present in PA females compared to healthy controls females: 49.1% versus 33.66%; p=0.041. Conclusion. Patients with noninvasive and nonrecurrence pituitary adenoma were the carriers of the C/C genotype significantly more frequently than their control counterparts and the C/T genotype in females was more frequent.